2019
DOI: 10.1063/1.5088557
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low electric field-driven dielectric tunability in hybrid ferroelectric (MV)[BiI3Cl2]

Abstract: Seeking for materials with high dielectric tunability and low coercive field is of great importance for the development and application of microwave tunable devices. In this work, inorganic and organic hybrid crystals (MV)[BiI3Cl2] were synthesized by using a solvothermal reaction method. Higher dielectric tunability (>70%) can be achieved for (MV)[BiI3Cl2] with an ultralow driving electric field (∼40 V/cm). The coercive electric field of (MV)[BiI3Cl2] is around three orders of magnitude lower than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…108,109,122 Of the nine crystals systems listed above, it was observed that some feature a syn coupling of polar chains; this results in high experimentally determined polarization values – similar to that observed for the well-known room temperature ferroelectric material (), (MV)[BiI 3 Cl 2 ]. 123 Another set of examples that involve linear or zigzag 1D chain-like architectures formed of pentagonal pyramidal MX 3 2− dianions in an environment of organic dications is shown in Fig. S20a–e of the ESI† section S.G.…”
Section: Statistical Analysis and Illustrative Crystal Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…108,109,122 Of the nine crystals systems listed above, it was observed that some feature a syn coupling of polar chains; this results in high experimentally determined polarization values – similar to that observed for the well-known room temperature ferroelectric material (), (MV)[BiI 3 Cl 2 ]. 123 Another set of examples that involve linear or zigzag 1D chain-like architectures formed of pentagonal pyramidal MX 3 2− dianions in an environment of organic dications is shown in Fig. S20a–e of the ESI† section S.G.…”
Section: Statistical Analysis and Illustrative Crystal Systemsmentioning
confidence: 99%
“…(MV)[BiI 3 Cl 2 ]. 123 Another set of examples that involve linear or zigzag 1D chain-like architectures formed of pentagonal pyramidal MX 3 2− dianions in an environment of organic dications is shown in Fig. S20a-e of the ESI † section S.G.…”
Section: (A) Bismuth Trihalides and Bi⋯x Pnbsmentioning
confidence: 99%
“…The dielectric constant of bulk ferroelectric materials on the DC bias electric field (E 0 ) exists the nonlinear dependence, which has potential use for phase shifters, filters, and so on. 18,19 However, there are no relevant studies in HIFs. In our previous work, we observed negative piezoelectric behaviors in Ca 3 Ti 2 O 7 and Na-doped Ca 3 Ti 2 O 7 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the leakage current information on Sr 3 Sn 2 O 7 ceramics was lacking in the literature and its mechanisms must be clarified. The dielectric constant of bulk ferroelectric materials on the DC bias electric field ( E 0 ) exists the nonlinear dependence, which has potential use for phase shifters, filters, and so on 18,19 . However, there are no relevant studies in HIFs.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, quasi-one-dimensional ferroelectric OIHP (MV)AI 3 Cl 2 (MV = methylviologen (C 12 H 14 Cl 2 N 2 ), A = Bi, Sb) have shown their potential applications in photovoltaic and high-density ferroelectric memory areas due to their high electron transport, low coercive field and strong optical absorption properties. [17][18][19] More importantly, large-scale (MV)AI 3 Cl 2 was synthesized using the hydrothermal method and the Curie temperature (T c ) of the ferroelectric phase was above room temperature. 20,21 These two advantages are conducive to the operation of devices at room temperature.…”
Section: Introductionmentioning
confidence: 99%